Coordination Behavior of a P4‐Butterfly Complex towards Transition Metal Lewis Acids: Preservation versus Rearrangement. Issue 11 (25th January 2021) - Müller, Julian; Scheer, Manfred
Abstract: The reactivity of the P4 butterfly complex [{Cp'''Fe(CO)2 }2 (μ, η 1:1 ‐P4 )] (1, Cp'''=η 5 ‐C5 H2 t Bu3 ) towards divalent Co, Ni and Zn salts is investigated. The reaction with the bromide salts leads to [{Cp'''Fe(CO)2 }2 (μ3, η 2:1:1 ‐P4 )MBr2 ] (M=Co (2Co ), Ni (2Ni ), Zn (2Zn )) in which the P4 butterfly scaffold is preserved. The use of the weakly ligated Co complex [Co(NCCH3 )6 ][SbF6 ]2, results in the formation of [{(Cp'''Fe(CO)2 )2 (μ3, η 4:1:1 ‐P4 )}2 Co][SbF6 ]3 (3 ), which represents the second example of a homoleptic‐like octaphospha‐metalla‐sandwich complex. The formation of the threefold positively charged complex 3 occurs via redox processes, which among others also enables the formation of [{Cp'''Fe(CO)2 }4 (μ5, η 4:1:1:1:1 ‐P8 ){Co(CO)2 }][SbF6 ] (4 ), bearing a rare octaphosphabicyclo[3.3.0]octane unit as a ligand. On the other hand, the reaction with [Zn(NCCH3 )4 ][PF6 ]2 yields the spiro complex [{(Cp'''Fe(CO)2 )2 (μ3, η 2:1:1 ‐P4 )}2 Zn][PF6 ]2 (5 ) under preservation of the initial structural motif. Abstract : Highly flexible : By coordination to Lewis acids the P4 butterfly complex can preserve the initial P4 butterfly scaffold and act as a 4σ e − donor. However, in the presence of weakly ligated d 6 metals, the P4 unit tends to rearrange. This leads to a rare octaphospha‐cobalt‐sandwich complex in which the P4 units have isomerized into aromatic cyclo ‐P4 [Fe]2 units ([Fe]=Cp'''Fe(CO)2 ). Additionally, also a dimerization to an all‐phosphorus derivative of bicylo[3.3.0]octane is observed.